2022
DOI: 10.21203/rs.3.rs-1228530/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Erythropoietin in Acute Kidney Injury (EAKI): a Pragmatic Randomized Clinical Trial

Abstract: Background Treatment with erythropoietin is well established for anemia in chronic kidney disease patients but not well studied in acute kidney injury.MethodsThis is a multicenter, randomized, pragmatic controlled clinical trial. It included 134 hospitalized patients with anemia defined as hemoglobin <11 g/dL and acute kidney injury defined as an increase of serum creatinine of 0.3 mg/dL within 48 hours or 1.5 times baseline. One arm received recombinant human erythropoietin 4000 UI subcutaneously every oth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…For instance, a recent multicentre pragmatic trial reported that treatment with erythropoietin (EPO) did not impact the need of transfusion, renal recovery, or mortality among anaemic acute kidney disease patients. In this trial, after patients were randomised to EPO and control groups, the investigators were allowed to manage the patients based on their usual real-world practice [42].…”
Section: Pragmatic Clinical Trialsmentioning
confidence: 99%
“…For instance, a recent multicentre pragmatic trial reported that treatment with erythropoietin (EPO) did not impact the need of transfusion, renal recovery, or mortality among anaemic acute kidney disease patients. In this trial, after patients were randomised to EPO and control groups, the investigators were allowed to manage the patients based on their usual real-world practice [42].…”
Section: Pragmatic Clinical Trialsmentioning
confidence: 99%
“…Brazilian Journal of Health Review, Curitiba, v. 6, n. 1, p.1239-1253, jan./feb., 2023 melhorou Fonte: autoral, com base nas referências consultadas para a revisão integrativa.Brazilian Journal of Health Review, Curitiba, v. 6, n. 1, p.1239-1253, jan./feb., 20234 DISCUSSÃOApós a leitura e análise dos resultados obtidos a partir dos diferentes estudos clínicos e randomizados, a discussão se fundamenta a partir de diferentes tópicos acerca de novos avanços e atualizações para a abordagem terapêutica da lesão renal aguda: Eritropoietina humana recombinante (rhEPO), Ácido ascórbico (AA), Curcuminóides, Biomarcador proteína de A eritropoietina humana recombinante (rhEPO), secretada pelas células tubulares renais, revolucionou o manejo da anemia da doença renal crônica (DRC), no entanto poucos estudos abordam o seu uso na anemia da lesão renal aguda (LRA), sendo o seu uso tido como controverso. Isso ocorre porque foi observado em experimentos que os níveis de eritropoetina aumentam nas primeiras 48 horas após a LRA, caindo progressivamente logo após(AOUN et al, 2022).Entretanto, em casos de LRA que cursem com hospitalizações duradouras, as transfusões se tornam necessárias, o que torna o seu uso controverso, tendo em vista que é essencial prevenir transfusões em pacientes com LRA. Isso ocorre porque o potencial de sensibilização decorrente das transfusões pode impedir futuros transplantes nesses pacientes.Pensar novas estratégias terapêuticas em casos de LRA que cursem com anemia, portanto, se torna essencial(AOUN et al, 2022).Pacientes que desenvolvem LRA pós-operatória apresentam um estágio de disfunção renal baixo e reversível.…”
unclassified
“…Isso ocorre porque foi observado em experimentos que os níveis de eritropoetina aumentam nas primeiras 48 horas após a LRA, caindo progressivamente logo após(AOUN et al, 2022).Entretanto, em casos de LRA que cursem com hospitalizações duradouras, as transfusões se tornam necessárias, o que torna o seu uso controverso, tendo em vista que é essencial prevenir transfusões em pacientes com LRA. Isso ocorre porque o potencial de sensibilização decorrente das transfusões pode impedir futuros transplantes nesses pacientes.Pensar novas estratégias terapêuticas em casos de LRA que cursem com anemia, portanto, se torna essencial(AOUN et al, 2022).Pacientes que desenvolvem LRA pós-operatória apresentam um estágio de disfunção renal baixo e reversível. A sua ocorrência está relacionada com maior mortalidade perioperatória, morbidade, maior tempo de internação e dos custos, bem como maior risco de Brazilian Journal of Health Review, Curitiba, v. 6, n. 1, p.1239-1253, jan./feb., 2023…”
unclassified